A Polymer Solution To Prevent Nanoclustering and Improve the Selectivity of Metal Nanoparticles for Electrocatalytic CO2 Reduction. Issue 44 (20th September 2019) - Zhang, Lei; Wei, Zichao; Thanneeru, Srinivas; Meng, Michael; Kruzyk, Megan; Ung, Gaël; Liu, Ben; He, Jie
Abstract: The stability of metal nanocatalysts for electrocatalytic CO2 reduction is of key importance for practical application. We report the use of two polymeric N‐heterocyclic carbenes (NHC) (polydentate and monodentate) to stabilize metal nanocatalysts (Au and Pd) for efficient CO2 electroreduction. Compared with other conventional ligands including thiols and amines, metal–carbene bonds that are stable under reductive potentials prevent the nanoclustering of nanoparticles. Au nanocatalysts modified by polymeric NHC ligands show an activity retention of 86 % after CO2 reduction at −0.9 V for 11 h, while it is less than 10 % for unmodified Au. We demonstrate that the hydrophobicity of polymer ligands and the enriched surface electron density of metal NPs through σ‐donation of NHCs substantially improve the selectivity for CO2 reduction over proton. Abstract : Ligands for nanocatalysts : Polymeric N‐heterocyclic carbene (NHC) ligands are demonstrated to stabilize Au and Pd nanoparticles for CO2 electroreduction while simultaneously enhancing their selectivity over competitive proton reduction.